Elevated pontine and putamenal GABA levels in mild-moderate Parkinson disease detected by 7 tesla proton MRS - Emir, U; Tuite, P; Öz, G (Public Library of Science, 2012)
Background Parkinson disease (PD) is characterized by the degeneration of nigrostriatal dopaminergic neurons. However, postmortem evidence indicates that the pathology of lower brainstem regions, such as the pons and medulla, precedes nigral involvement. Consistently, pontomedullary damage was implicated by structural and PET imaging in early PD. Neurochemical correlates of this early pathological involvement in PD are unknown. Methodology/Principal Finding To map biochemical alterations in the brains of individuals with mild-moderate PD we quantified neurochemical profiles of the pons, putamen and substantia nigra by 7 tesla (T) proton magnetic resonance spectroscopy. Thirteen individuals with idiopathic PD (Hoehn & Yahr stage 2) and 12 age- and gender-matched healthy volunteers participated in the study. γ-Aminobutyric acid (GABA) concentrations in the pons and putamen were significantly higher in patients (N = 11, off medications) than controls (N = 11, p<0.001 for pons and p<0.05 for putamen). The GABA elevation was more pronounced in the pons (64%) than in the putamen (32%). No other neurochemical differences were observed between patients and controls. Conclusion/Significance The GABA elevation in the putamen is consistent with prior postmortem findings in patients with PD, as well as with in vivo observations in a rodent model of PD, while the GABA finding in the pons is novel. The more significant GABA elevation in the pons relative to the putamen is consistent with earlier pathological involvement of the lower brainstem. This study provides in vivo evidence for an alteration in the GABAergic tone in the lower brainstem and striatum in early-moderate PD, which may underlie disease pathogenesis and may provide a biomarker for disease staging.